THE COMPOSITION, BOUNDARIES, AND BIOMASS OF THE BIOSPHERE (Лучшие интеллектуальные исследования, 2025)
ABSTRACT:        The biosphere encompasses all regions of the Earth where life exists, integrating the atmosphere, lithosphere, and hydrosphere. This paper discusses the composition of the biosphere, including living organisms and the physical environment that supports life. It also examines the spatial boundaries that define the biosphere and analyzes global biomass distribution across different ecosystems. Understanding the biosphere's structure and biomass is essential for ecological research and sustainable environmental management.